Participation and its impact on rationalizing strategic decision-making - applied research in the Middle Euphrates Electricity Directorate - Kamel Shukair Al-Watifi (Iraqi Journal for Administrative Sciences, 2025)
Strategic decisions are characterized by great importance and a clear impact on the future of organizations, and the issue of involving the organization’s resources, especially its middle staff, in the process of making and rationalizing these decisions is no less important. Based on this importance, the current research addressed the extent of administrative leadership’s participation in rationalizing strategic decision-making, and began The research consists of main hypotheses about the impact and relationship between the independent variable (participation) and the dependent variable (strategic decisions). The research hypotheses were tested in an important organization in the life of the citizen (the Middle Euphrates Electricity Directorate), and the research concluded that there is a correlation and a significant influence relationship between participation. Administrative leadership and rationalization of strategic decision-making. The research included a recommendation to the administration on the necessity of qualifying its cadres and enhancing their participation in the subject of strategic decision-making.